EVALUATION OF ROOT TRAINERS AS ALTERNATIVE CONTAINERS TO POLYBAGS FOR RAISING LITCHI AIR LAYERS USING VARIOUS POTTING MEDIA - GUPTA, RUCKU; ARTI SHARMA; RAFIQ AHMAD SHAH, PARSHANT BAKSHI; V. K.WALI (The Bioscan, 2018)
A study was done to evaluate the growth and survival raising litchi air layers in root trainers, polybags and nursery beds with different containers viz. small sized polybags (10x5.5inch), large sized polybags (12x8.5inch) and root trainers (500cc). Each type of container was filled with four different growing media viz., soil: sand: compost in the ratio of 1:1:1 and 1:1:2 and soil: sand: sphagnum moss in the ratio of 1:1:1 and 1:1:2. Among various treatments, large sized polybags containing soil: sand: sphagnum moss in the ratio of 1:1:2, showed maximum plant height (28.55cm), stem diameter (0.84cm), number of leaves (27.58), and shoots (6.47), shoot fresh weight (20.47g) and dry weight(10.48g), leaf fresh (4.61g) and dry weight (2.65g) and maximum survival (95.5%) after six months of transplanting. Root trainers (500 cc) containing soil: sand: sphagnum moss in the ratio of 1:1:2, shows highest length of primary root (22.68 cm), number of primary roots (31.74), and secondary roots (32.36), root fresh (4.58 g) and dry weight (0.47g). Although root trainers show less survival (73.3%) than polybags (95.5%), but because of their eco-friendly, reusable and light nature these can prove a profitable technology for raising litchi air layers in the current scenario of environmental hazard.